Representing the Battle of Zama to Create an Iconic Event*. (2014) - Billot, Frances
Abstract: This article compares the use of certain literary, structural and historical features by Polybius, Livy and Silius Italicus in their representations of the battle of Zama in 202 BC between the Romans and Carthaginians. It is argued that through their application of these features they present the battle as an iconic event and position it as a grand finale to the Second Punic War. The comparisons highlight some of the literary constructs in Polybius' Histories and illustrate how some later authors adapt and possibly respond to Polybius' presentation. Similarities in presentation to emphasise the importance of the battle do not necessarily mean that the authors convey the same message over the long term effects of its outcome. For example, where Polybius' special treatment of the battle of Zama, Hannibal and Scipio reflects his belief in the pivotal role the Roman victory played in changing the balance of power across the ancient Mediterranean world (15.9.2, 10.2), Silius Italicus' special treatment may also be read as presenting the outcome of the battle in terms of causing a shift in power balance, in this case within the city of Rome, and leading to the development of the principate and the one-man rule of imperial Rome (17.653-4, 3.261-4).